Bortezomib in newly diagnosed multiple myeloma patients (Hematology Meeting Reports, 2009)
High-dose therapy represents today the standard of care for younger multiple myeloma (MM) patients candidates to transplant. The induction phase is performed usually with VAD or VAD-like schemes which, however, produce a complete remission rate (CR) in less than 10%. Bortezomib (Velcade®) has demonstrated to be very effective in relapsed/refractory myeloma patients giving as single agent a CR rate of 16%, and several evidences indicate that bortezomib shows a synergistic activity with dexamethasone or other cytotoxic agents. Thus, taking into account that the achievement of a CR is the main objective in the treatment of MM, it is reasonable to introduce Bortezomib (Velcade®) as part of front-line high-dose programs. The application of bortezomib to novel front-line therapies depends in part on its effects on subsequent stem cell mobilization and engraftment.